Examining the Contribution of a CELTA Course to the Development of ESL Students’ Vocabulary via Consideration of the Guided Discovery Sheet Method - Dr , Somanchi Sai Kumar (International Journal of Psychosocial Rehabilitation, 2015)
The goal of the present research is to use the guided discovery sheet as a method that primarily focuses on the MPF of the target language. The CELTA course I completed this past summer represented the culmination of my efforts to develop a global English language-teaching profession, and the guided discovery sheets I used with my students gave them the freedom to do so with the guidance I had gleaned from my own teaching practise sessions. The "Certificate in Teaching English to Speakers of Other Languages" (CELTA) is a programme administered by Cambridge Assessment English at Cambridge University. The methodology for this research was used during the academic year (1442 - 1443 H) to teach a course titled "Effective Academic Writing 2" to students in the second year of their studies at the College of Arts in Dr BR Amedkar University in Andhra Pradesh. After that, the researcher switched to a quGiritative methodology, conducting interviews with the same 33 students using the online learning management system Blackboard. The advantages and disadvantages of using a guided discovery sheet to study foreign language vocabulary are addressed in the interview questions. Participants agreed that the method was engaging and helpful in learning the blocked vocabulary in an appeGiring manner, and they advocated its use in all academic writing courses